UJI BEBERAPA KONSENTRASI EKSTRAK BUAH MENGKUDU (Morinda citrifolia L.) TERHADAP PENYAKIT ANTRAKNOSA YANG DISEBABKAN OLEH JAMUR COLLETOTRICHUM CAPSICI PADA BUAH CABAI MERAH PASCAPANEN - Muhammad Ali; Fifi Puspita; Molehet M. Siburian (Universitas Riau, 2012)
A research has been conducted to study the effect of some concentrations of Noni (Morindacitrifolia L.) fruit extract in controlling anthracnose disease, caused by Colletorichum capsici on thepost-harvested red chilli fruits. The research has been conducted experimentally using a CompletelyRandomized Design consisting of 5 treatments and 4 replications. The treatments are someconcentrations of noni fruit extract : 0%=Mo, 5%=M1,10%=M2,15%=M3 and 20%=M4. Result of theresearch indicated that the concentration of noni fruit extract gave a significantly different effect incontrolling anthracnose disease on post-harvested red chilli fruits. The concentration of noni fruit extractat 20% showed a better effect in controlling anthracnose disease on post-harvested red chilli fruits whichresulted in a smaller in-vitro colony growth of the causal fungal pathogen, a longer incubation period ofthe disease and a lower disease intensity.